Hilar Arteriovenous Pattern in a Case of Horseshoe Kidney - Miorin, Ana Paula Gobate; Cabral, Rôksanny Carneiro Carrijo; Bellini, Rafael; Batigália, Fernando; Chacon, Erivelto Luís; Boer, Nagib Pezati (Journal of Morphological Sciences, 2018)
Horseshoe kidney is a poor congenital formation that results in the union of the lower poles of the kidneys through the fibrous isthmus that crosses the median line, with a prevalence of 0.25% (1 in 400 births), a higher rate in males (2:1 or 3:1), and an important variation in the arrangement of arteries and veins in the hilum. The present study aims to describe the arteriovenous pattern in the renal hilum in a case of horseshoe kidney. A conventional retroperitoneal dissection was performed in a 64-year-old female corpse of brown skin color, legally belonging to the Anatomy Laboratory of Unicastelo, Fernandópolis, state of São Paulo, Brazil, with causa mortis associated with uterine cancer. The dissection revealed a horseshoe kidney, with the right kidney measuring 5.69 cm, the left kidney measuring 11.65 cm, and the isthmus measuring 6.40 cm, and with the presence of a single right superior polar segmental artery (originated in the posterior aspect of the renal artery), of a double left superior polar segmental artery (originated in the renal artery, with one for each renal aspect), of one renal isthmus artery (originated in the posterior aspect of the abdominal aorta), and of one renal isthmus vein (left common iliac vein). Horseshoe kidney is a congenital abnormality whose arteries may originate from branches of the renal artery, of the inferior mesenteric artery, or of the iliac artery. Its veins drain into the renal vein, into the inferior vena cava, or into the iliac vein. It may be associated with hydronephrosis and nephroblastoma. However, no reports in the literature are found regarding the correlation with uterine cancer, highlighting the relevance of the hilar vascular pattern of the reported case.
Keywords: horseshoe kidney; anomaly; artery; vein; anatomy